Effect of Nebivolol and Olmesartan on 24-Hour Brachial and Aortic Blood Pressure in the Acute Stage of Ischemic Stroke - Eleni Georgianou; Panagiotis I. Georgianos; Konstantinos Petidis; Konstantinos Markakis; Ioanna Zografou; Asterios Karagiannis (International Journal of Hypertension)
Background. Elevated blood pressure (BP) in the acute phase of ischemic stroke is associated with heightened risk of early disability and death. However, whether BP-lowering in this setting is beneficial and the exact levels at which BP should be targeted remain unclear. This study aimed to evaluate the effect of nebivolol, olmesartan, and no-treatment on 24-hour BP in patients with hypertension during the acute poststroke period. Methods. In a single-blind fashion, 60 patients with acute ischemic stroke and clinic systolic BP (SBP) 160–220 mmHg were randomized to nebivolol (5 mg/day), olmesartan (20 mg/day), or no-treatment between Day 4 and Day 7 of stroke onset. BP-lowering efficacy was assessed through 24-hour BP monitoring using the Mobil-O-Graph device (IEM, Germany). Results. Between baseline and Day 7, significant reductions in 24-hour brachial SBP were noted with nebivolol and olmesartan, but not with no-treatment. Change from baseline (CFB) in 24-hour brachial SBP was not different between nebivolol and olmesartan groups (between-group difference: −3.4 mmHg; 95% confidence interval (CI): −11.2, 4.3), whereas nebivolol was superior to no-treatment in lowering 24-hour brachial SBP (between-group difference: −7.8 mmHg; 95% CI: −7.8 mmHg; 95% CI: −15.6, −0.1). Similarly, nebivolol and olmesartan equally lowered 24-hour aortic SBP (between-group difference: −1.9 mmHg; 95% CI: −10.1, 6.2). Nebivolol and olmesartan provoked similar reductions in 24-hour heart rate-adjusted augmentation index and pulse wave velocity. Conclusion. This study suggests that during the acute phase of ischemic stroke, nebivolol is equally effective with olmesartan in improving 24-hour aortic pressure and arterial stiffness indices. ClinicalTrials.gov identifier number: NCT03655964.